APPLYING FAIR VALUE TO REFLECT AND TO RECORD BIOLOGICAL ASSETS IN FORESTRY COMPANIES - Vu Hai, Hoang; Tien Thao, Nguyen (Journal of Forestry Science and Technology, 2017)
This paper emphasizes the context and the method of fair value measurement according to International Financial Reporting Standards No 13 (IFRS 13). The term "fair value" is a new concept in Vietnam because of the dominant application of historical cost. Vietnam has gradually updated the fair value method, with historical cost method to assess each kind of asset at timing of financial statement. In addition, the historical cost is defined as basic concept in accounting, so that the role of fair value is quite faint. In forestry companies, plantation forest is considered as a special asset due to the value of forest varies as the growth of trees, which results in the using of historical cost approach to reflect and record biological value is unreasonable. Therefore, it is necessary to understand and apply fair value to measure plantation forest’s value.